Reference values for haematological and biochemical profile in adult Indian buffaloes - Dhillon, Kanwarpal Singh; Randhawa, Charanjit Singh; Gupta, Kuldip; Singh, Raj Sukhbir; Chhabra, Sushma (Buffalo Bulletin, 2020)
The study was conducted on 187 graded Niliravi and Murrah buffaloes, 1 to 15 years, representing 15 districts of Punjab. Blood samples were collected two times from each buffalo. Mean values TEC, TLC, absolute lymphocyte numbers and activity of creatine kinase were higher in pregnant and non-pregnant heifers. Total serum bilirubin was higher in lactating pregnant buffaloes compared to lactating non-pregnant buffaloes. There was no difference (P≤0.05) in red cell parameters, platelet count, total leukocytes count (TLC), differential leukocyte counts (DLC), total serum protein, albumin, total bilirubin, cholesterol, plasma fibrinogen, aspartate aminotransferase (AST), alkaline phosphokinase (ALKP), gamma-glutamyl transferase (GGT), creatine kinase (CK), sodium (Na), potassium (K) and calcium (Ca) and iron metabolism analytes when compared by breed, parity and milk yield. Reference values were expressed as mean, standard deviation, range, reference intervals (5th to 95th percentiles) and as 95% confidence intervals of mean. The established reference values will be useful for the interpretation of haematolgical and biochemical profile for clinical diagnosis in buffaloes in the region.